Enhanced transduction and replication of RGD-fiber modified adenovirus in primary T cells. - Sadhak Sengupta; Ilya V Ulasov; Bart Thaci; Atique U Ahmed; Maciej S Lesniak (PLoS ONE)
Background Adenoviruses are often used as vehicles to mediate gene delivery for therapeutic purposes, but their research scope in hematological cells remains limited due to a narrow choice of host cells that express the adenoviral receptor (CAR). T cells, which are attractive targets for gene therapy of numerous diseases, remain resistant to adenoviral infection because of the absence of CAR expression. Here, we demonstrate that this resistance can be overcome when murine or human T cells are transduced with an adenovirus incorporating the RGD-fiber modification (Ad-RGD). Methodology/principal finding A luciferase-expressing replication-deficient Ad-RGD infected 3-fold higher number of activated primary T cells than an adenovirus lacking the RGD-fiber modification in vitro. Infection with replication-competent Ad-RGD virus also caused increased cell cycling, higher E1A copy number and enriched hexon antigen expression in both human and murine T cells. Transduction with oncolytic Ad-RGD also resulted in higher titers of progeny virus and enhanced the killing of T cells. In vivo, 35-45% of splenic T cells were transduced by Ad-RGD. Conclusions Collectively, our results prove that a fiber modified Ad-RGD successfully transduces and replicates in primary T cells of both murine and human origin.